Food hardness preference reveals multisensory contributions of fly larval gustatory organs in behaviour and physiology - Komarov, Nikita; Fritsch, Cornelia; Maier, G. Larisa; Bues, Johannes; Biočanin, Marjan; Avalos, Clarisse Brunet; Dodero, Andrea; Kwon, Jae Young; Deplancke, Bart; Sprecher, Simon G. (PLOS Biology, 2025)
Sensing food is a complex multisensory experience. This study of food hardness preference in fruit fly larvae reveals that gustatory organ sensory neurons can perceive cues of both chemical and mechanical stimulation.